ChemInform Abstract: A Green Approach for Highly Regioselective Syntheses of Furo[3, 2‐h]quinolines in Aqueous Medium. Issue 43 (7th October 2013) - Sarkar, Swarbhanu; Pal, Rammyani; Chatterjee, Nivedita; Dutta, Samrat; Naskar, Subhendu; Sen, Asish Kumar
Abstract Furoquinolines are prepared from hydroxyquinolines and alkynes via a copper‐free Sonogashira coupling/cycloisomerization sequence in aqueous micellar medium under aerobic conditions.